Faculty of Business and Management, UiTM Kampus Alor Gajah, Melaka / Arief Nur Ihsan Ismail - Ismail, Arief Nur Ihsan (Faculty of Office Management and Technology, 2025)
This report presents an overview of my six-month internship at the Faculty of Business and Management, UiTM Kampus Alor Gajah, Melaka, from 12 August 2024 to 24 January 2025. Throughout the internship, I was responsible for various administrative tasks, including filing, managing correspondence, photocopying, and providing assistance to lecturers. These duties allowed me to gain hands-on experience in office operations, ensuring that I contributed effectively to the smooth functioning of the faculty's daily activities. My role also involved interacting with faculty staff and students, enhancing my communication skills and adaptability in a professional environment. During the internship, I focused on improving key competencies such as organization, multitasking, and problem-solving. Flandling administrative tasks required attention to detail and efficiency, particularly when managing document flow and ensuring accurate record-keeping. Moreover, assisting lecturers with their academic needs and handling various administrative requests allowed me to understand the academic processes behind faculty management, which was instrumental in broadening my understanding of the educational sector. Overall, this internship provided me with a well-rounded experience in office management within an academic institution. The exposure to real-world administrative work, coupled with the guidance of faculty staff, significantly improved my practical skills and professional manner. I would like to extend my heartfelt thanks to the Faculty of Business and Management (FBM) for providing me with the opportunity to intern at UiTM. My deepest gratitude goes to Dr. Siti Normah Awang Tuah, Dr. Anidah Aziz, and Encik Maz Izuan Mazalan for their continuous guidance and support throughout this journey. I am also grateful to all FPP lecturers who have been supportive and contributed to making this internship a truly enriching and rewarding experience. This experience has prepared me to handle future challenges in administrative roles, further strengthening my foundation for a successful career in office and business management.